Digitalni podatki - Ciglič, Rok; Geršič, Matjaž; Perko, Drago; Zorn, Matija (GIS v Sloveniji, 2016)
Digitalni podatki ('Digital Data') is the thirteenth volume in the series GIS v Sloveniji (GIS in Slovenia). The goal of this volume is to present the wide variety of research findings on geographical information systems in Slovenia in recent years. Digital data is one of the main pillars of geographical information systems, and so this volume describes opportunities to put such data to use. Recently lidar scanning technology has increased the precision and diversity of analysis. The volume clearly presents project results and research in areas such as geography, hydrology, protection against natural disasters, archaeology, transport, settlement, remote sensing, and others. Readers will discover new features regarding GIS applicability and learn about interesting findings in these areas.